Prawie globalna erozja katolicyzmu - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2022)
The almost global erosion of Catholicism is a research hypothesis based on the analysis of decades of data collected by the global social science research initiative World Values Survey. It provided hard data on the condition of Catholicism. Analyzing such at-titudes as anti-Semitism, xenophobia, and homophobia, it can be concluded that they are not only prtesent in the mentality and attitudes of many Catholics, but we can observe also the intensification of such attitudes in some countries. However, it must also be stated that there are trends leading to the changes that were initiated at the Second Vatican Council. They rejoice in the last years, when Jorge Maria Bergoglio became pope in 2013, taking the name of Francis, the official support of the Vatican. Only a few such changes will be mentioned as harbingers of deeper processes, the consequences of which we are not yet aware of.